Numerical investigations of magnetic field effects on electrodeposition - Ní Mhíocháin, Teresa (Trinity College (Dublin, Ireland). School of Physics, 2002)
Electrodeposits are fractal in nature when grown in a flat electrochemical cell, in which an aqueous solution of salt of a metal such as Cu, Zn or Ag is held between an anode and cathode by two flat sheets of perspex. These fractals undergo dramatic changes in their morphologies when grown in the presence of a perpendicular applied magnetic field. In the case of a central cathode encircled by a ring anode, deposits become spiral rather than radial in appearance, while the stringy deposits grown between two linear electrodes tilt markedly.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin